Geologi Daerah Motilango, Kabupaten Gorontalo, Provinsi Gorontalo - Polontalo, Moh. Afandi; Permana, Aang Panji; Aris, Ayub Pratama; Ninasafitri, Ninasafitri (Journal of Applied Geoscience and Engineering, 2023)
Mapping is an activity carried out by geologists to describe the types of rock that make up it, the structure and history of the formation of an area. The research method used is a combination of qualitative and quantitative methods consisting of literature study, field data collection, data analysis and processing, and research reporting. Geomorphological results of the research area consist of hill units in fault zones, intrusive hill units, and denudational hill units with little erosion. The stratigraphy is composed of the youngest to oldest units: andesite lava units, basalt lava units, and diorite units. The structure consists of a primary structure, namely tarpaulin joints and secondary structures, namely tensile joints and shear joints, which result in the main stress direction being northwest-southeast, and shearing to the left. Geological history began in the Middle Miocene from the formation of diorite intrusive rock (Tmb) which then produced Bilungala Volcanic rock (Tpmb (l)) which was composed sequentially from basalt lava which then became andesite lava. During the Pliocene period, a tectonic phase trending northwest-southeast occurred and produced types of thrust faults and left-slip faults (sinistral). The research area is an active volcanic area with intrusive and extrusive rocks which are thought to have the same source. The influence of tectonic subduction in the Sulawesi Sea is an activity that damages the research area apart from human activity.